Familial bladder cancer and the related genes - Hemminki, Kari; Lorenzo Bermejo, Justo; Ji, Jianguang; Kumar, Rajiv (Current opinion in urology, 2011)
Purpose of review - Family history of bladder cancer is a known risk factor for bladder cancer but new data have emerged on the influence of a family history of other tumours than bladder cancer. Recent data have shown that family history influences survival of bladder cancer. Gene identification has been successful particularly on low-risk genes influencing susceptibility and prognosis. - Recent findings - Familial clustering of bladder cancer has been found with cancers of the stomach, larynx, kidney, endometrium and the bone marrow (leukaemia). Shared smoking habits are an explanation to these findings and between spouses these appear to be the only explanation to the clustering of cancers with bladder cancer. Family members also share prognosis of bladder cancer, either good or poor survival. Among the low-penetrant genes, the variants within the genes encoding metabolic enzymes have been consistently associated with susceptibility to bladder cancer and the evidence is compelling for NAT2 slow acetylator and GSTM1 null genotypes. - Summary - Smoking is the only identifiable environmental factor explaining familial clustering of bladder cancers and other cancers. Genetic factors are likely to contribute to many of the described associations but the identified genes are probably an introduction to the genetics of bladder cancer.
Gesehen am 12.10.2022